Effects of gama irradiation on nucellar callus production of lhe 'Valência' sweet orange (Citrus sinsensis) Osb. in vitro. - Pasqual, Moacir; Ando, Akihiko (Pesquisa Agropecuaria Brasileira, 2014)
The conventional methods of plant breeding have not given a significative contribution for the citrus breeding. A precious iniprovement by the techniques of tissues culture in vitro, associated with induced mutations, is expected. Nucelli extracted from developping fruits with twelve weeks after pollination were cultured in vitro, on medium supplemented (in mg/ 1) by: thiamine HCQ 0.2; piridoxine HCL 1.0;  icotinic acid 1.0; mesoinositol 100; malt extract; sucrose 50.000; and agar 8.000 with pi-! = 5.7. The irradiation at 0.0; 0.5; 1.0; 2.0; 4.0; 8.0 and 12.0 kR doses was applied on, only medium, only nucellus, and medium and nucellus together. Irradiation of only nucellus and both nucellus and medium, at the same time, showed similar effects. Low doses of irradiation (until 2 kR) decrease the number of differential embryoids. The irradiation of culture medium, mainly at high doses, increases callus proliferation
Keywords: tissues culture; CO; nucellar tissues; citrus; mutations induction.